Opening, Solution, Despair: Why Turkey Still Faces a Kurdish Question - Altaras, Nesi (Tufts Archival Research Center, 2019)
Between 2009 and 2015, the government of Turkey made two distinct attempts at solving its multifaceted Kurdish question. What happened in this period? Why did these attempts fail and what are the necessary conditions for this question to be solved?